The compensatory nature of moral damages in investor-state arbitration - Jarrod Wong (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2013)
The failure of investment tribunals to grasp the compensatory nature of moral damages awarded to investors has led to doctrinal and practical difficulties in the treatment of moral damages. Many such difficulties can be addressed by identifying the specific moral injury suffered – whether mental or reputational – and awarding commensurate compensation rather than satisfaction, restitution or punitive damages.
Keywords: 330